Paternal H3K4 methylation is required for minor zygotic gene activation and early mouse embryonic development - Aoshima, Keisuke; Inoue, Erina; Sawa, Hirofumi; Okada, Yuki (EMBO reports, 2015)
Epigenetic modifications, such as DNA methylation and histone modifications, are dynamically altered predominantly in paternal pronuclei soon after fertilization. To identify which histone modifications are required for early embryonic development, we utilized histone K‐M mutants, which prevent endogenous histone methylation at the mutated site. We prepared four single K‐M mutants for histone H3.3, K4M, K9M, K27M, and K36M, and demonstrate that overexpression of H3.3 K4M in embryos before fertilization results in developmental arrest, whereas overexpression after fertilization does not affect the development. Furthermore, loss of H3K4 methylation decreases the level of minor zygotic gene activation (ZGA) predominantly in the paternal pronucleus, and we obtained similar results from knockdown of the H3K4 methyltransferase Mll3/4. We therefore conclude that H3K4 methylation, likely established by Mll3/4 at the early pronuclear stage, is essential for the onset of minor ZGA in the paternal pronucleus, which is necessary for subsequent preimplantation development in mice. Synopsis In the mouse zygote, transcriptional properties are asymmetric between male and female pronuclei. This study shows that in the male pronucleus, minor zygotic gene activation requires Mll3/4‐dependent H3K4 monomethylation likely at enhancers. Overexpression of H3.3 K4M mutant in the zygote causes global reduction of paternal H3K4 methylation, minor zygotic transcription, and subsequent embryonic development. Mll3/4, responsible enzymes for H3K4 monomethylation at enhancer regions, are involved in paternal minor ZGA. Graphical Abstract In the mouse zygote, transcriptional properties are asymmetric between male and female pronuclei. This study shows that in the male pronucleus, minor zygotic gene activation requires Mll3/4‐dependent H3K4 monomethylation likely at enhancers.